2019
DOI: 10.1016/j.vaccine.2018.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Development of a valid and reliable scale to assess parents’ beliefs and attitudes about childhood vaccines and their association with vaccination uptake and delay in Ghana

Abstract: Background: Parents’ attitudes and beliefs in vaccination are important to understand for shaping vaccine acceptance and demand interventions. Little research has focused on developing a validated scale to measure parents’ attitudes towards vaccinations in low and middle-income countries; Ghana provided an opportunity develop a caregiver vaccination attitudes scale (CVAS) validated against childhood vaccine compliance. Methods: We conducted a cluster survey of 373 households with children aged 12–35 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
2
50
1
Order By: Relevance
“…Ten items were used to measure negative attitudes toward vaccination. Six were adapted from Wallace et al (2019) and four items were constructed by the authors. Participants indicated their agreement on a 5-point scale.…”
Section: Health-related Beliefsmentioning
confidence: 99%
“…Ten items were used to measure negative attitudes toward vaccination. Six were adapted from Wallace et al (2019) and four items were constructed by the authors. Participants indicated their agreement on a 5-point scale.…”
Section: Health-related Beliefsmentioning
confidence: 99%
“…Current research in Ghana has revealed that in some settings using Likert-type anserwing formats (eg, 1 = I totally agree, 7 = I totally disagree) may be a challenge for the participants. 15 Changing to other formats (eg, 1=no, 2=undecided, 3=yes) seems advisable to reduce error variance. For the scoring, calculate a mean score across items per antecedent.…”
Section: Cmentioning
confidence: 99%
“…Vaccine safety research is an important component of public health program [ 8 , 9 , 10 , 11 ]. Some scholars discussed the mutual restriction and interaction between the government and drug enterprises in the game process in order to find the reasons for the existence of unsafe drug incidents and put forward countermeasures [ 12 ]. Literature [ 13 , 14 ] discussed the game relationship between the government and production enterprises, local governments, and social supervision, and then put forward corresponding countermeasures from the aspects of strengthening supervision, clarifying the relationship between regulatory departments and local governments, and promoting the application of new technologies.…”
Section: Introductionmentioning
confidence: 99%